Rancang Bangun Sistem Integrasi Web Service Menggunakan Metode Enterprise Servicebus pada Universitas Jambi - Mahaarta, Minata Putra; Marzal, Jefri; Mauladi, Mauladi (Prodi Sistem Informasi FST Universitas Jambi, 2018)
This research aims to create a system integration using web service that is used to facilitate and facilitate the existing system at jambi university in doing data transaction. The information system that is integrated in this research is, academic information system (SIAKAD), sms broadcast information system, information system of research and service institution (LPPM) and electronic financial information system (ePayment). This integration system was developed using the Enterprise Service Bus (ESB) method. System integration is designed and built by utilizing Anypoint Studio applications. Web service development passes the requirement stage, design analysis from service provider side and service user, implementation, and testing. The testing of this web service integration system refers to Quality of Service (QoS). Web service testing is done by request on each service as much as ± 100, ± 500, ± 1000 and with the request frequency is set at 500ms. The results of web service testing built found that, the measurement of web service performance based on time responders have an average time value below 1.5 seconds. Testing the level of web service availability obtained the value of the highest success rate of 100% and the lowest 94%, this is due to the large amount of data and server capabilities in data processing.